Choroidal and retinal structural, cellular and vascular changes in a rat model of Type 2 diabetes - Campos, António (2021)
Increasing evidence points to inflammation as a key factor in the pathogenesis of diabetic retinopathy (DR). Choroidal changes in diabetes have been reported and several attempts were made to validate in vivo choroidal thickness (CT) as a marker of retinopathy. We aimed to study choroidal and retinal changes associated with retinopathy in an animal model of spontaneous Type 2 diabetes, Goto-Kakizaki (GK) rats. Sclerochoroidal whole mounts and cryosections were prepared from 52-week-old GK and age-matched control Wistar Han rats. CT was measured by optical coherence tomography. Microglia reactivity, pericyte and endothelial cells distribution, and immunoreactivity of vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2) were evaluated by immunofluorescence. Choroidal vessels were visualized by direct perfusion with 1,1'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate (Dil). Choroidal vascular density was evaluated by fluorescence microscopy. GK rats had increased CT (58.40 ± 1.15 μm versus 50.90 ± 1.58 μm, p < 0.001), reduced vascular density of the choriocapillaris (CC) (p = 0.045), increased Iba1+ cells density in the outer retina (p = 0.003) and increased VEGFR2 immunoreactivity in most retinal layers (p = 0.021 to 0.037). Choroidal microglial cells and pericytes showed polarity in their distribution, sparing the innermost choroid. This cell-free gap in the inner choroid was more pronounced in GK rats. In summary, GK rats have increased CT with decreased vascular density in the innermost choroid, increased VEGFR2 immunoreactivity in the retina and increased Iba1+ cells density in the outer retina.